-8(5n+9)=11n

Simple and best practice solution for -8(5n+9)=11n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(5n+9)=11n equation:


Simplifying
-8(5n + 9) = 11n

Reorder the terms:
-8(9 + 5n) = 11n
(9 * -8 + 5n * -8) = 11n
(-72 + -40n) = 11n

Solving
-72 + -40n = 11n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-11n' to each side of the equation.
-72 + -40n + -11n = 11n + -11n

Combine like terms: -40n + -11n = -51n
-72 + -51n = 11n + -11n

Combine like terms: 11n + -11n = 0
-72 + -51n = 0

Add '72' to each side of the equation.
-72 + 72 + -51n = 0 + 72

Combine like terms: -72 + 72 = 0
0 + -51n = 0 + 72
-51n = 0 + 72

Combine like terms: 0 + 72 = 72
-51n = 72

Divide each side by '-51'.
n = -1.411764706

Simplifying
n = -1.411764706

See similar equations:

| 5xn-18-4xn=36 | | 2.5x+1.5=-9.5 | | 9=19x+39-4x | | 4(t-5)-3=6t-13 | | 12-3(5x-7)-4x=71 | | 0.75x+0.2x=x-2 | | 25-x=7 | | (wx)2= | | 3(8-3(1))=5(2+1) | | 7z=180-22 | | (8-3(1))=5(2+1) | | 27x^3-1= | | 9x^2-28x+3=0 | | -3p+7=6-10p-5 | | 9x+7=3x-9 | | 2r-6r=12 | | -(c-12c-c-3c)= | | 4(b+3)=24 | | -18-6k=6(p-8) | | x(3x+11)=20 | | 12+z-x= | | 6m^3n^3*8m^2n^3= | | 4b+2=6b-6 | | (8-3(1))= | | 2X+8+3X= | | -56=4-5x | | 7(x-2)+2(x+4)+27=180 | | -14b+28=-10b+30 | | 13m=11 | | 6x+5=-7+4x+24 | | 6x^4=5 | | x.x-x=2x-2 |

Equations solver categories